A Literature Highlight: How A Traceability System Can Support Halal Supply Chain? - Resista Vikaliana; Yuli Evitha; Cundo Harimurti; Laode Sabaruddin; Aziza Leila Komala (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
At present, halal awareness is related to food quality, both in Muslim countries and non-Muslim countries. Food safety and quality assurance of food integrity, including food safety, health, nutrition and quality. The concept of halal includes process control, packaging, storage and delivery. All activities involved in the supply chain, especially food, the question is whether the integrity of halal food products can remain halal throughout the supply chain. Halal traceability, namely recording all information on activities in producing products from upstream, namely the origin of raw materials to downstream, becomes important. This literature review aims to determine the halal traceability system in the halal food supply chain. In particular, this article discusses the traceability architecture in food products. The study suggest some topics of emphasis in developing an economic research gate: Break even point of Halal traceability and tracking, acceptable level of risk in Halal traceability and tracking, participation in Halal traceability and tracking system. The ‘shades’ of food  integrity in the halal supply chain are oﬀered, which can be categorized into four supply chain dimensions, related to raw materials, production, service, and the consumer.